Bio-inspired algorithm optimization of neural network for the prediction of Dubai crude oil price - Haruna, Chiroma; Abdul-Kareem, Sameem; Saadi, Younes; Khan, Abdullah; Abubakar, Adamu; Abdullahi Muaz, Sanah; Ya’u Gital, Abdulsalam; Mohd Shuib, Nor Liyana (Springer Nature Singapore, 2019)
Previous studies proposed several bio-inspired algorithms for the optimization of Neural Network (NN) to avoid local minima and to improve accuracy and convergence speed. To advance the performance of NN, a new bio-inspired algorithm called Flower Pollination Algorithm (FPA) is used to optimize the weights and bias of NN due to its ability to explore very large search space and frequent chosen of similar solution. The FPA optimized NN (FPNN) was applied to build a model for the prediction of Dubai crude oil price unlike previous studies that mainly focus on theWest Texas Intermediate and Brent crude oil price benchmarks. Results